2016
DOI: 10.1080/15384101.2016.1189040
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of monocyte induced cell migration by the RNA binding protein, FXR1

Abstract: FXR1 belongs to a family of RNA-binding proteins that play critical roles in post-transcriptional regulation of gene expression in immunity, development and cancer. FXR1 is associated with regulation of specific mRNAs in myocytes and macrophages. In quiescent cells (> 24 h of extended serum-starvation, »30-48 h or more), a spliced isoform of FXR1, FXR1a, promotes translation of the cytokine TNFa, independent of the effects of RNA levels. Here we examined the role of FXR1 in THP1 human monocytic leukemic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
(132 reference statements)
1
23
0
Order By: Relevance
“…STAT is well established in regulating cytokine gene transcription. We have also observed that FXR1 knockdown inhibited the expression of multiple cytokines (data not shown), consistent with a recent report of FXR1 function in positively regulating cytokine expression in monocytes ( Le Tonqueze et al, 2016 ). Notably, only about 0.7–1.57% of the STAT1/3 peaks overlap with FXR1 peaks in our ChIP-seq study, suggesting that FXR1 only participates in the transcription of a very small fraction of JAK-STAT target genes.…”
Section: Discussionsupporting
confidence: 92%
“…STAT is well established in regulating cytokine gene transcription. We have also observed that FXR1 knockdown inhibited the expression of multiple cytokines (data not shown), consistent with a recent report of FXR1 function in positively regulating cytokine expression in monocytes ( Le Tonqueze et al, 2016 ). Notably, only about 0.7–1.57% of the STAT1/3 peaks overlap with FXR1 peaks in our ChIP-seq study, suggesting that FXR1 only participates in the transcription of a very small fraction of JAK-STAT target genes.…”
Section: Discussionsupporting
confidence: 92%
“…However, TP53 is frequently mutated in the disease, allowing tumour cells to escape cell cycle arrest and continue proliferating , which can also lead to increased resistance to chemo‐ and radiotherapy . FXR1 may support this evasion of arrest through negative regulation and/or destabilisation of p21 and stabilisation of telomerase RNA component (TERC) activity in vitro .…”
Section: Identification Of Pro‐oncogenic Factors In 3q26‐29mentioning
confidence: 99%
“…This is exemplified by the recent approval of pembrolizumab. FXR1 may have a putative role in the innate immune response through positive regulation of the proinflammatory cytokines C‐C motif‐chemokine ligand 2 (CCL2) and interleukin 1 beta (IL1β) in monocytes . CCL2 mRNA is significantly upregulated in HNSCC compared to normal human keratinocytes and is secreted by HNSCC tumour cells to recruit peripheral monocytes and macrophages.…”
Section: Identification Of Pro‐oncogenic Factors In 3q26‐29mentioning
confidence: 99%
“…Taking into consideration the fact that FXR1 forms SDS-resistant conformers and strongly colocalizes with Thioflavin S, we can conclude that this protein is present in rat brain in amyloid form under native conditions. It is known that FXR1 binds to different RNA molecules that form secondary structures and affects their level and translation efficiency (25). We suggested that amyloid conformers of FXR1 may protect RNA from action of ribonucleases that normally present in eukaryotic cells and take part in a gene expression control.…”
Section: Fxr1 Forms Functional Amyloid Conformers In Brain That Bind mentioning
confidence: 97%